Tay bridge and extracellular‐regulated kinase activity are required for motoneuron function in the Drosophila neural system. (15th April 2018) - Molnar, C.; Estrada, B.; de Celis, J. F.
Abstract : Extracellular regulated kinase (Erk) activity is required during neural development for the specification of cell fates in neuroblasts and neuronal lineages, and also regulates several aspects of the activity and survival of mature neurons. The activation of Erk is regulated at multiple levels by kinases and phosphatases that alter its phosphorylation state and by other proteins that regulate its subcellular localization. Here, we find that tay bridge ( tay ), a negative regulator of Erk in Drosophila imaginal discs, is required in the motoneurons to regulate the number and size of neuromuscular synapses in these cells. The expression of Tay is maximal in motoneurons with low levels of activated ERK, suggesting that Tay modulates the activity of Erk in these cells. We also found that loss of tay expression and increased Erk activity specifically in the motoneurons cause a reversible decrease in walking speed. Impaired motoneurons activity may be caused by alterations in the functionality and number of synaptic boutons developing at the neuromuscular junction in tay mutants. Abstract :